Unraveling the potential human health risks from used disposable face mask-derived micro/nanoplastics during the COVID-19 pandemic scenario: A critical review - Li, Minghui; Hou, Zongkun; Meng, Run; Hao, Shilei; Wang, Bochu (Environment international, 2022)
[Display omitted] •MPs and NPs will be releasesd from DFMs during environmental degradation.•DFM-derived MPs/NPs could cause human multi-organ toxicity.•DFM-derived MPs/NPs serve as carriers of toxic chemicals and pathogens.•Advanced human organoids provide promising models for DFM-derived MP/NP toxicity assessment.•Innovative approaches and eco-friendly strategies are urgently demanded to reduce DFM-derived MP/NP pollution. With the global spread of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), disposable face masks (DFMs) have caused negative environmental impacts. DFMs will release microplastics (MPs) and nanoplastics (NPs) during environmental degradation. However, few studies reveal the release process of MPs/NPs from masks in the natural environment. This review presents the current knowledge on the abiotic and biotic degradation of DFMs. Though MPs and NPs have raised serious concerns about their potentially detrimental effects on human health, little attention was paid to their impacts on human health from DFM-derived MPs and NPs. The potential toxicity of mask-derived MPs/NPs, such as gastrointestinal toxicity, pneumotoxicity, neurotoxicity, hepatotoxicity, reproductive and transgenerational toxicity, and the underlying mechanism will be discussed in the present study. MPs/NPs serve as carriers of toxic chemicals and pathogens, leading to their bioaccumulation and adverse effects of biomagnification by food chains. Given human experiments are facing ethical issues and animal studies cannot completely reveal human characteristics, advanced human organoids will provide promising models for MP/NP risk assessment. Moreover, in-depth investigations are required to identify the release of MPs/NPs from discarded face masks and characterize their transportation through the food chains. More importantly, innovative approaches and eco-friendly strategies are urgently demanded to reduce DFM-derived MP/NP pollution.